2008
DOI: 10.1016/j.pain.2007.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Transition from acute to chronic pain and disability: A model including cognitive, affective, and trauma factors

Abstract: This study evaluated a theoretically and empirically based model of the progression of acute neck and back pain to chronic pain and disability, developed from the literature in chronic pain, cognition, and stress and trauma. Clinical information and standardized psychosocial measures of cumulative traumatic events exposure (TLEQ), depressed mood (CES-D), pain (DDS), physical disability (PDI), and pain beliefs (PBPI) were collected at baseline from 84 acute back pain patients followed at an Acute Back Clinic ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(132 citation statements)
references
References 57 publications
8
118
0
6
Order By: Relevance
“…Our finding also concurs with the view that the psychosocial factor is one predictor for chronic musculoskeletal pain in office workers 16,45) . In this study, several work-related psychosocial factors, including psychological job demands, decision latitude, supervisor support, coworker support, physical job demands, job security, and hazards at work, were evaluated using the Job Content Questionnaire.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding also concurs with the view that the psychosocial factor is one predictor for chronic musculoskeletal pain in office workers 16,45) . In this study, several work-related psychosocial factors, including psychological job demands, decision latitude, supervisor support, coworker support, physical job demands, job security, and hazards at work, were evaluated using the Job Content Questionnaire.…”
Section: Discussionsupporting
confidence: 92%
“…The present study only sourced patients whose current episode was less than six weeks, and the average time since onset of the baseline assessment was less than three weeks. Studies that have found depression a useful predictor have used a less strict inception cohort 24,25,26,29 or collected data sometime after the initial consultation 27 . In support of this view, we found that depression measured at six weeks was significantly correlated with chronic disability.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Although some reported that persistent pain should be considered as a disease, a key feature of pain is its subjectivity 1) . Furthermore, psychological factors such as more cumulative traumatic life events, higher levels of depression in the early stages of a new pain episode, and early beliefs that pain may be permanent significantly contribute to increased severity of subsequent pain and disability 4,23) . Psychological factors have been reported to be predictive of long-term disability for many pain syndromes as well as for pain severity, emotional distress, and treatment seeking 16,19) .…”
Section: Discussionmentioning
confidence: 99%